Surface‐Mediated Synthesis of Dimeric Rhodium Catalysts on MgO: Tracking Changes in the Nuclearity and Ligand Environment of the Catalytically Active Sites by X‐ray Absorption and Infrared Spectroscopies. Issue 4 (3rd December 2012) - Yardimci, Dicle; Serna, Pedro; Gates, Bruce C.
Abstract The preparation of dinuclear rhodium clusters and their use as catalysts is challenging because these clusters are unstable, evolving readily into species with higher nuclearities. We now present a novel synthetic route to generate rhodium dimers on the surface of MgO by a stoichiometrically simple surface‐mediated reaction involving [Rh(C2H4)2] species and H2. X‐ray absorption and IR spectra were used to characterize the changes in the nuclearity of the essentially molecular surface species as they formed, including the ligands on the rhodium and the metal‐support interactions. The support plays a key role in stabilizing the dinuclear rhodium species, allowing the incorporation of small ligands (ethyl, hydride, and/or CO) and enabling a characterization of the catalytic performance of the supported species for the hydrogenation of ethylene as a function of the metal nuclearity and ligand environment. A change in the nuclearity from one to two Rh atoms leads to a 58‐fold increase in the catalytic activity for ethylene hydrogenation, a reaction involving unsaturated, but stable, dimeric rhodium species.